Cultivation, varietal structure and possibilities for cross-pollination of Brassica napus L. in Slovenia - Barbara PIPAN; Jelka ŠUŠTAR-VOZLIČ; Vladimir MEGLIČ (Acta Agriculturae Slovenica)
Oilseed rape, Brassica napus L., is one of the most important oil plants of the moderate climatic zone and a typical industrial plant. In the past, dynamics of oilseed rape production in Slovenia was reflected in flexible agricultural market situation because of introduction of new crops into rotation and due to financial supports from European Union. In 2010, it was cultivated on 5351ha, accounting for about 1.1% of the total production areas in Slovenia. It is mainly grown in the eastern part of Slovenia (Pomurje, Podravje) and in the Spodnje-Posavska region. From 1984 until 2010, 58 different genotypes of oilseed and fodder rape were grown in Slovenia, of which a total of 28 were registered in the National List of Varieties in each year. Average yield of oilseed rape was ranged between 1.8 and 2.9 t/ha. Under Slovenian fragmented property structure the cross-pollination between B. napus and volunteer or feral populations (within and outside the production area) can occur. In addition to that, the presence of some sexually compatible relatives which have a high affinity to cross-pollination with B. napus are found (B. rapa, B. oleracea, B. nigra, Hirchfeldia incana, Raphanus raphanistrum, Sinapis arvensis, Diplotaxis erucoides, D. tenuifolia, D. muralis, S. alba, R. sativus and Rapistrum rugosum). Uncontrolled gene flow between different forms of B. napus or sexually compatible wild relatives in the case of coexistence of different production systems has a direct impact on the varietal purity of seeds and on crop quality.